Lao PDR Economic Monitor, April 2008 - World Bank (World Bank, Vientiane, 2013)
Lao PDR's economic outlook remains favorable, with continued strong growth. Gross domestic product (GDP) growth remained at above 7 percent in 2007. Output expanded in mining, newly emerging processing industries, agriculture, and new construction of hydropower projects, tourism and other services. Non-resource sectors contributed over 5 percent to this growth, and the resource sector around 2.5 percent. As Lao PDR is surrounded by some of the fastest growing economies in the world, it has benefited from increased demands for its products and large FDI inflows from neighboring countries, such as China, Vietnam and Thailand. The macroeconomic situation remained fairly stable, but is at risk of rising inflation. After falling to a record low level of 4.5 percent in 2007, overall inflation climbed to 6.4 percent in February 2008. High fuel prices pushed up the costs of transportation for individuals and households, construction (including imported raw materials and other chemical related products), land clearing and agricultural farming (including processing materials). The kip nominal exchange rates appreciated almost by 9 percent against US$ and was steady against the Thai baht during the last six to months from Oct 2007 to Mar 2008. It reports on recent economic performance (Part I), progress in the implementation of the Government's policy reform agenda (Part II), and donor activities in the relevant reform areas (Part III).